2016
DOI: 10.1016/j.gca.2015.11.019
|View full text |Cite
|
Sign up to set email alerts
|

A spatially resolved surface kinetic model for forsterite dissolution

Abstract: The development of complex alteration layers on silicate mineral surfaces undergoing dissolution is a widely observed phenomenon. Given the complexity of these layers, most kinetic models used to predict rates of mineral-fluid interactions do not explicitly consider their formation. As a result, the relationship between the development of the altered layers and the final dissolution rate is poorly understood. To improve our understanding of the relationship between the alteration layer and the dissolution rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 74 publications
(129 reference statements)
4
50
1
Order By: Relevance
“…As such, during the early stages of these experiments, the preferential initial release of light Mg is still evident in the fluid phase and negligible isotopic equilibration can occur by the return of material back to the hydromagnesite. Note that a similar initial release of isotopically light divalent metals to the aqueous phase has been observed during forsterite, basaltic glass, and pyrite dissolution (Verney-Caron et al, 2011;Oelkers et al, 2015;Maher et al, 2016;Wolfe et al, 2016). Some preferential departure of light Mg from hydromagnesite could arise from isotopic heterogeneity of the hydromagnesite used in the experiments.…”
Section: The Temporal Evolution Of Fluid and Mineral Mg Isotope Compomentioning
confidence: 59%
“…As such, during the early stages of these experiments, the preferential initial release of light Mg is still evident in the fluid phase and negligible isotopic equilibration can occur by the return of material back to the hydromagnesite. Note that a similar initial release of isotopically light divalent metals to the aqueous phase has been observed during forsterite, basaltic glass, and pyrite dissolution (Verney-Caron et al, 2011;Oelkers et al, 2015;Maher et al, 2016;Wolfe et al, 2016). Some preferential departure of light Mg from hydromagnesite could arise from isotopic heterogeneity of the hydromagnesite used in the experiments.…”
Section: The Temporal Evolution Of Fluid and Mineral Mg Isotope Compomentioning
confidence: 59%
“…Both Pokrovsky and Schott 25 and Palandri and Kharaka 22 already suggested that for slightly alkaline solutions (e.g., seawater), forsterite dissolution at steady-state is controlled by the decomposition of a protonated surface complex, which is silica-rich and magnesium-deficient. Maher et al 32 postulate that olivine dissolution occurs as a series of boundary layer processes, in which primary dissolution of cations is followed by dissolution of silicic acid ions, which may subsequently repolymerize at the surface. This implies that the measured dissolved silica release rate is a net value, which may not serve as the sole proxy for olivine dissolution.…”
Section: Discussionmentioning
confidence: 99%
“…When olivine is added to coastal waters, potential pore water saturation in the seabed and secondary reactions will likely occur (Montserrat et al, ). In addition, the alternating layers (Mg‐poor layers, SiO 4 ‐coatings) generated on the olivine mineral surface can lead to nonstoichiometric dissolution (the number of dissolved atoms cannot be expressed as a ratio presented in the chemical formula) and temporal variations of the area‐normalized olivine dissolution rates (Maher et al, ). Since a detailed understanding of these processes under typical seawater conditions is currently lacking, these complex interactions are ignored in our study.…”
Section: Methodsmentioning
confidence: 99%